Border movements applied to the clinical assessment of malocclusions: A literature review (Research, Society and Development, 2023)
Orthodontic diagnosis requires a prior assessment of the patient's mandibular position, which is generally carried out in Centric Relation and Maximum Initial Intercuspation. The present study aims to evaluate the possibility of applying bordering movements as an alternative to the positions of Centric Relation and Maximum Initial Intercuspation. This is a literary review. The searches for scientific evidence were carried out in the following databases: Virtual Health Library, Scientfic Electronic Library Online and PubMed, using the search terms: Functional Occlusion, Diagnosis and Orthodontics. Initially, 2396 articles were identified. After selection, 7 were suitable for the objective of the study. It was found that studies aimed at applying functional occlusion in orthodontics in terms of mandibular positioning for an initial diagnostic criterion, present spaces and a temporal cut, for the most part, prior to the year 2006. It is concluded that it is possible to use the bordering movements as a guide to guide mandibular positioning for orthodontists, replacing the Centric Relation, however, more clinical studies on this topic are needed, mainly focused on orthodontic diagnosis.